Prince Caspian : the return to Narnia - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperEntertainment, 2008)
Peter, Edmund, Susan, and Lucy help Prince Caspian organize his army of Talking Beasts to fight against an evil king who has taken control of Narnia.
Maps on endpapers.
6.1
5-8
5-8
870
Keywords: Narnia (Imaginary place) -- Juvenile fiction; Princes -- Juvenile fiction; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Fantasy; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Fantasy fiction; Movie novels